Regulating constitutional complaint cases is the authority of the constitutional court - Ni Ketut Sari Adnyani; I Wayan Landrawan; Dewa Ayu Eka Agustini (Jurnal Civics: Media Kajian Kewarganegaraan)
This research aims to determine the constitutional rights of citizens through constitutional complaints based on the authority of the Constitutional Court from the perspective of Constitutional Law. Types of normative juridical research with a statutory, conceptual, and case approach. The data sources used are primary, secondary and tertiary legal materials. The research results show that constitutional complaints as the authority of the Constitutional Court have become an urgent need to be enforced in the Unitary State of the Republic of Indonesia. The authority for constitutional complaints to the Constitutional Court is eliminated, the legal implication of which is to create protection for the human rights of Indonesian citizens from actions by government officials or individuals who injure citizens' human rights and recognition of the Constitution. The Court as an institution has the authority to submit constitutional complaints to the Constitutional Court. Authorised institution. Guardian of the Constitution. The Constitutional Court protects the constitutional rights of citizens if their constitutional rights are violated by the provisions of the law so that the law is then declared to be contrary to the Constitution. The possibility of violations of citizens' constitutional rights does not only occur through normative provisions in law. There are many ways and opportunities for citizens' constitutional rights violations, whether by the authorities or other parties. This is where we learn the importance of the Constitutional Complaints mechanism at the Constitutional Court.